AN INTEGRATION OF PROPHETIC ECO-LITERATION VALUE AS AN ELABORATION OF ENVIRONMENTAL LOVE EDUCATION IN INDONESIAN LANGUAGE TEACHING MATERIALS - Qurrota Ayu Neina; Subyantoro Subyantoro; Rahayu Pristiwati; U'um Qomariyah; Restu Aditia (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2023)
This study aims to substantially discuss the principles of integrating prophetic eco-literacy values in Indonesian Language teaching materials. Particularly, this research will analyze the principle of integration aimed at a low-quality class of elementary school students as a form of elaboration of environmental love education, so that students have a moral spirit to conserve the environment. This research uses the R and D research procedures from Borg and Gall. This research focuses on the first and second steps, namely (a) research and information collecting and  (b) planning. The results of the adaptation of this research step are, 1) an initial study that includes a needs analysis and 2) the development of principles of integrating prophetic eco-literacy values as a form of elaboration of environmental love education in Indonesian Language teaching materials for a low-quality class of elementary schools. The results showed that there were values of tauhid, khilafah, syariah, and amanat in the basic competencies contained in the low-quality class of elementary school curriculum. The principles of preparing Indonesian Language teaching materials containing prophetic ecological values are manifested in several indicators, including: 1) analysis of teaching material needs, 2) preparation of teaching materials, 3) structure of teaching materials, and 4) preparation of teaching materials.